Czech Republic : Report on Observance of Standards and Codes FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The Czech government has made impressive progress in bringing the antimoney laundering (AML) regime of the Czech Republic into compliance with both European and international standards. The Czech government has undertaken important steps toward completing the legal and institutional framework to fight money laundering, and has begun concrete implementation of the AML regime in the various relevant financial sectors. Further efforts by the government to improve the country's AML legal and institutional framework and effective supervision have resulted in the enactment of major legislation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet